Physical equivalency of wild type and galactose α 1, 3 galactose free porcine pericardium; a new source material for bioprosthetic heart valves. (1st September 2016) - McGregor, Christopher; Byrne, Guerard; Rahmani, Benyamin; Chisari, Elisa; Kyriakopoulou, Konstantina; Burriesci, Gaetano
Graphical abstract: Abstract: Humans make high levels of antibody to carbohydrates with terminal galactose α 1, 3 galactose (Gal) modifications. This Gal antigen is widely expressed in other mammals and is present on an array of current animal derived biomedical devices including bioprosthetic heart valves. There is growing interest in using Gal-free animal tissues from Gal knockout pigs (GTKO) as these tissues would not be affected by anti-Gal antibody mediated injury. In this study we compare the composition and biophysical characteristics of glutaraldehyde fixed porcine pericardium from standard and GTKO pigs. We show that with the exception of the Gal antigen which is only present in standard pig tissue both GTKO and standard pig tissue have the same general morphology and collagen content. Moreover uniaxial stress testing and suture retention testing indicate the tissues are equivalent in tensile strength. These studies indicate that genetic disruption of the α-galactosyltransferase (GGTA-1) which blocks synthesis of the Gal antigen has no significant impact on the structural integrity of porcine pericardium and suggest that this tissue could be directly substituted for standard pig pericardium in biomedical devices such as bioprosthetic heart valves. Statement of Significance: Surgical heart valve replacement is a proven life saving therapy to treat heart valve dysfunction due to birth defects, infection and the effects of aging. Bioprosthetic heart valves (BHV) made from glutaraldehyde fixed animal tissues are an effective durable therapy in older patients (>60 years) but exhibit age-dependent structural valve degeneration (SVD) in younger patients (<60 years). SVD is principally caused by BHV calcification. Immune injury contributes to age-dependent SVD through the interaction of galactose α 1, 3 galactose (Gal) a dominant xenogeneic antigen present on commercial BHVs and universally abundant human anti-Gal antibody. This study measures the tissue equivalency between standard pig pericardium and Gal-free pericardium from genetically modified pigs as a first step towards making Gal-free BHVs.